PENDIDIKAN UNTUK APA? - Maman A. Djauhari (Fakultas Seni Rupa dan Desain ITB, 2006)
Education is one of the elements that is worth considering besides science and technology in order to put Indonesia to the same level as the one of the developed nations have reached. The importance of education in the Sundanese ethnic values is prominent, which gives priority to a man having an education. It is expressed in its songs and rhymes. Further, the values say that education will help a man interact with others fully well. Moreover, in its broader sense, education will ultimately lead the people of a nation to defend their country. However, the current facts show that education in Indonesia tends to shape someone to give priority on strengthening his/his family's/his clan's own economy combined with a hedonistic and consumptive life style. All of these will lead to the negative impacts to the nation's resilience. Therefore, the future education of Indonesia must be committed to the nation identity and resilience besides science and technology.